Synthesis of Zeolite A from Iraqi Natural Kaolin Using a Conventional Hydrothermal Synthesis Technique (UKH Journal of Science and Engineering, 2020)
The synthesis of zeolite materials by hydrothermal transformation of kaolin using a conventional hydrothermal method was investigated. Different analytical techniques were used to characterize the starting kaolin and produced zeolite A samples, including scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), x-ray diffraction (XRD), x-ray fluorescence (XRF), thermogravimetric analysis (TGA), and Fourier transform infrared (FT-IR) spectroscopy. The synthetic zeolite type A was obtained after activation of kaolin and metakaolin followed by different thermal and chemical treatments. The metakaolinization phase was achieved by calcining the kaolin in air at 600°C for 3 hours, a much lower temperature than previously reported in the literature. Metakaolin was treated with 3 M sodium hydroxide solution at a ratio of 1:5 and, using stainless steel autoclaves with teflon liners, heated the mixture to 200°C in a microwave for 24 hours. The results from this synthesis route showed that zeolite A with a cubic crystal habit has been successfully synthesized.